Linking smallholder production with value-added food markets - Begashaw, Belay; Verburg, Gert-Jan; Yamauchi, Futoshi; Fettibene, Daniele; Fujita, Yasuo (T20, 2019)
Demographic pressures and climate change in Africa are rendering subsistence farming an unviable livelihood strategy for smallholder farmers. However, urbanization and economic growth are creating new markets for fresh and processed foods in the region. To enter this market, African smallholders need to adopt new production strategies that will increase income and make farming more appealing to the next generation. The G20 can encourage this transition by supporting the growth of a rural-based food processing sector, the reorientation of smallholder agriculture to commercialization, and the development of infrastructure to link farmers to markets.